INTERVAL VALUED FUZZY SOFTMATRICES IN DIABETES - et al., Dr .T. Geetha (International Journal of Advanced Science and Technology, 2019)
Diagnosis is a major task in medical science. Therefore, medical diagnosis is an art of evaluating a person's body's pathological conditions from all the available signs. Soft set is really a modern mathematical approach that is developing to solve unpredictability.Portrayal of the unclear and reliable information of medical documentation is dealt with in real world.